2017
DOI: 10.3390/rs9070755
|View full text |Cite
|
Sign up to set email alerts
|

Landsat 15-m Panchromatic-Assisted Downscaling (LPAD) of the 30-m Reflective Wavelength Bands to Sentinel-2 20-m Resolution

Abstract: Abstract:The Landsat 15-m Panchromatic-Assisted Downscaling (LPAD) method to downscale Landsat-8 Operational Land Imager (OLI) 30-m data to Sentinel-2 multi-spectral instrument (MSI) 20-m resolution is presented. The method first downscales the Landsat-8 30-m OLI bands to 15-m using the spatial detail provided by the Landsat-8 15-m panchromatic band and then reprojects and resamples the downscaled 15-m data into registration with Sentinel-2A 20-m data. The LPAD method is demonstrated using pairs of contemporan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 63 publications
0
9
0
1
Order By: Relevance
“…This means that the ARD are not resampled twice. This is advantageous as resampling degrades the geometric fidelity, either by introducing pixel shifts (for nearest neighbor resampling), or by smoothing the data (e.g., bilinear resampling) and/or introducing artefacts at high contrast edges (e.g., cubic convolution resampling) [14,15]. The utility of reprojecting the data directly into Albers is illustrated in Figure 1 that shows (top) ARD data (i.e., resampled once) and (middle) the equivalent data nearest neighbor resampled from Collection 1 UTM into the Albers projection (i.e., resampled twice).…”
Section: Ard Projectionmentioning
confidence: 99%
“…This means that the ARD are not resampled twice. This is advantageous as resampling degrades the geometric fidelity, either by introducing pixel shifts (for nearest neighbor resampling), or by smoothing the data (e.g., bilinear resampling) and/or introducing artefacts at high contrast edges (e.g., cubic convolution resampling) [14,15]. The utility of reprojecting the data directly into Albers is illustrated in Figure 1 that shows (top) ARD data (i.e., resampled once) and (middle) the equivalent data nearest neighbor resampled from Collection 1 UTM into the Albers projection (i.e., resampled twice).…”
Section: Ard Projectionmentioning
confidence: 99%
“…The Sentinel-2 and the Landsat-8 data are registered to sub-pixel precision using affine transformations derived with a robust matching algorithm developed for this purpose [45] and via a least-squares adjustment among different orbits to reduce sensitivity to missing and cloudy data typically found when registering only individual tiles and images [46]. Research to downscale Landsat 8 30 m data to 20 m Sentinel 2 MSI resolution is underway [47] but currently the MSI 20 m data are upscaled to 30 m by bilinear resampling and the Landsat 8 Collection1 data are also bilinear resampled.…”
Section: Landsat-8 and Sentinel-2 Burned Area Mappingmentioning
confidence: 99%
“…Temporal enhancement is a key requirement, but spatial enhancement is another aspect of Landsat that could be improved for time series applications. Enhancement of spatial resolution has been carried out mostly based on data fusion methods [4][5][6][7]. Studies have also shown that data fusion can lead to improvements in quantitative remote sensing applications such as land cover [4,8,9].…”
Section: Introductionmentioning
confidence: 99%